2022
DOI: 10.1002/pen.26225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization ofPES/PSF/PEGby immersion precipitation for Mediterranean seawater desalination byFOmembrane

Abstract: In the present study, a simple, inexpensive, nontoxic, and environmentally friendly polyethylene glycol (PEG) polymer was used to enhance the hydrophilicity of the forward osmosis (FO) membrane using various PEG concentrations as a pore forming agent in the casting solution of polyethersulfone/polysulfone (PES/PSF) blend membranes. A nonwoven PES/PSF FO blend membrane was fabricated via the immersion precipitation phase inversion technique. The membrane dope solution was cast on polyethylene terephthalate (PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The feed solution and the draw solution in the experiment were DI water and 1 M NaCl aqueous solution, respectively. The AL-DS orientation was selected due to the serious concentration polarization when using AL-FS orientation. As shown in Figure , the water flux of the control TFC group is approximately 5.58 LMH, which is comparable to the commercial FO membranes under the same experimental conditions. APTMS-TFN0.01 exhibited the highest water flux of up to 18.52 LMH, which is 231.90% higher than that of the TFC FO membrane (5.58 LMH) and 45.25% higher than that of the pristine TFN membrane (12.75 LMH), followed by APTMS-TFN0.05 numbered as high as 18.14 LMH. The enhanced water fluxes can be attributed to the incorporation of modified TiO 2 nanoparticles in the PA active layer, possibly due to the combined effect of increased hydrophilicity (Table ).…”
Section: Resultsmentioning
confidence: 92%
“…The feed solution and the draw solution in the experiment were DI water and 1 M NaCl aqueous solution, respectively. The AL-DS orientation was selected due to the serious concentration polarization when using AL-FS orientation. As shown in Figure , the water flux of the control TFC group is approximately 5.58 LMH, which is comparable to the commercial FO membranes under the same experimental conditions. APTMS-TFN0.01 exhibited the highest water flux of up to 18.52 LMH, which is 231.90% higher than that of the TFC FO membrane (5.58 LMH) and 45.25% higher than that of the pristine TFN membrane (12.75 LMH), followed by APTMS-TFN0.05 numbered as high as 18.14 LMH. The enhanced water fluxes can be attributed to the incorporation of modified TiO 2 nanoparticles in the PA active layer, possibly due to the combined effect of increased hydrophilicity (Table ).…”
Section: Resultsmentioning
confidence: 92%
“…The incorporation of appropriate additives into the casting solution, implementation of supplementary procedures, and integration of chemical processes with the phase separation process may yield the desired qualities in the polymeric membrane. 23 Polyethersulfone (PES), as an engineering polymer, with excellent chemical resistance, good thermal stability, good mechanical properties, excellent film-forming properties, and well enough solubility in different solvents, is mostly used as a membrane material for preparation of forward osmosis (FO), 24 MF, UF, 25 NF, and RO membranes. [26][27][28][29] Poolachira et al indicated that permeate flux of the PES/GO/ polyvinylpyrrolidone (PVP) membrane is 150.2 L m À2 h À1 , and eight times higher than that of the unmodified membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethersulfone (PES), as an engineering polymer, with excellent chemical resistance, good thermal stability, good mechanical properties, excellent film‐forming properties, and well enough solubility in different solvents, is mostly used as a membrane material for preparation of forward osmosis (FO), 24 MF, UF, 25 NF, and RO membranes 26–29 …”
Section: Introductionmentioning
confidence: 99%
“…In the NIPS process, pores are easy to extract from the solid membrane surface, and they are often used for hydrophobic membrane modification to significantly improve the wettability of the membrane surface. Due to its difficult-to-control branched structure, it is easy to come out of the membrane, and mixing with the membrane matrix will produce an uneven pore structure, thereby affecting the screening performance of the membrane. However, the poor binding ability of inorganic nanomaterials to matrix materials will lead to unstable membrane modification.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its difficult-to-control branched structure, it is easy to come out of the membrane, and mixing with the membrane matrix will produce an uneven pore structure, thereby affecting the screening performance of the membrane. 31 34 However, the poor binding ability of inorganic nanomaterials to matrix materials will lead to unstable membrane modification.…”
Section: Introductionmentioning
confidence: 99%